SHIP PERFORMANCE INVESTIGATION DUE TO DEADRISE MODIFICATION: A CASE STUDY PASSENGER SHIP - Ariani, Betty; Ariesta, Rizky Chandra; Wildani, Ahmad; Hakim, M. Hanifuddin; Oktaviani, Marista (Journal of Applied Engineering Science, 2023)
Speed is the main factor that is always considered when designing a ship. Also, a ship designer will try to make a good design regarding the ship’s fuel efficiency and seakeeping performance. One example is the operation of passenger ships on the Ketapang – Gilimanuk crossing route in Bali, Indonesia. The Bali strait area has uncertainty waves and ocean currents; the determination of environmental characteristics is needed for an investigation. In this paper, a review is carried out on the primary parameters of ship hydrodynamics performance, i.e., hull changes to reduce ship resistance by modifying the bilge radius from angles of 10º, 15º, and 20º. This modification affects the geometric parameters. Two indicators are used to measure the effect of changes: resistance and seakeeping performance. Numerical methods were used to obtain the results, the calculation of the resistance was approached by the Holtrop process of investigation, and the NORDFORSK criteria validated the feasibility seakeeping assessment. The results of model Z show that when the deadrise angle is large, the ship reduces the resistance by approximately 8.2% at a service speed of 12 knots. Therefore, modification of the hull by raising the radius of the bilge results in a reduction in resistance, which affects the ship’s rolling, but with an increase in speed, it can reduce the heave and pitch significantly with the resulting hull with good performance obtained.